The bright long-lived Type II SN 2021irp powered by aspherical circumstellar material interaction: II. Estimating the CSM mass and geometry with polarimetry and light curve modeling - Reynolds, Thomas M.; Nagao, Takashi; Maeda, Keiichi; Elias-Rosa, Nancy; Fraser, Morgan; Gutierrez, Claudia; Kangas, Tuomas; Kuncarayakti, Hanindyo; Mattila, Seppo; Pessi, Priscila J. (EDP Sciences, 2026)
Context
There is evidence of interaction between supernova (SN) ejecta and massive circumstellar material (CSM) among various types of SNe. The mass-ejection mechanisms that produce a massive CSM are unclear. Therefore, studying interacting SNe and their CSM can shed light on these mechanisms and the final stages of stellar evolution.
Aims
We aim to study the properties of the CSM in the bright, long-lived, hydrogen-rich (Type II) SN 2021irp, which is interacting with a massive aspherical CSM.
Methods
We present imaging and spectro-polarimetric observations of SN 2021irp. Modelling its polarisation and bolometric light curve allowed us to derive the CMS mass and distribution.
Results
SN 2021irp shows a high intrinsic polarisation of ∼0.8%. This high continuum polarisation suggests an aspherical photosphere created by an aspherical CSM interaction. Based on the bolometric light curve evolution and the high polarisation, SN 2021irp can be understood as a typical Type II SN interacting with a CSM disc with a corresponding mass-loss rate and half-opening angle of ∼0.035–0.1 M⊙ yr−1 and ∼30–50°, respectively. The total CSM mass we derived is ≳2 M⊙. We suggest that this CSM disc was created by some process related to binary interaction and that SN 2021irp is the end product of a typical massive star (i.e. with a ZAMS mass of ∼8 − 18 M⊙) that has a separation and/or mass ratio with its companion star which has led to an extreme mass ejection within decades of explosion. We propose that the particular spectroscopic properties of SN 2021irp and similar SNe can be explained through a a Type II SNe interacting with a massive disc CSM.